MENINGKATKAN KUALITAS PETERNAKAN LOKAL: DISKUSI TERBUKA MANAJEMEN PEMELIHARAAN KAMBING DI DESA TINABOGAN KABUPATEN TOLITOLI - Aisyah Aisyah; Supamri Supamri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
Tinabogan Village in Tolitoli Regency has great potential for goat farming development, but still faces various challenges in goat husbandry management. This community service activity aims to improve the capacity of farmers through a participatory approach in the form of open discussions. The method used refers to the Participatory Rural Appraisal (PRA) concept, with stages including problem identification, conducting discussion forums, and evaluating and developing recommendations. The activity was held at the Tinabogan Village Hall and involved 22 local farmers and resource persons from the Madako University Tolitoli Community Service Program (KKN) team. The discussion results revealed key issues such as suboptimal feeding, poor pen sanitation, limited animal health services, and the lack of production records. The discussion forum also generated several local solutions and good practices that can be directly implemented by farmers. This activity demonstrates that a dialogic and participatory approach can improve farmers' practical knowledge and strengthen collaboration between actors. Thus, open discussions are an effective medium for promoting sustainable empowerment in the rural livestock sector,